Republic of the Marshall Islands : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2006)
This Selected Issues paper outlines economic developments in the Republic of the Marshall Islands (RMI) since independence in 1986, focusing on the challenges posed by dependence on foreign grants, and progress toward achieving budgetary self-reliance. Like most other Pacific islands, the RMI faces a variety of geographical constraints, including limited land area, poor soil, the dispersion of the islands, and the remoteness from major markets. The public sector plays a dominant role in the economy, backed by external assistance. The private economy remains underdeveloped, primarily providing services to the government.